Challenges and Future Perspective of Gastroretentive Mucoadhesive Dosage Forms - Akbar, Rayhan; Setiawan, Heri; Maggadani, Baitha Palanggatan; Iswandana, Raditya; Setio Putri, Kurnia Sari (UI Scholars Hub, 2024)
Gastroretentive Mucoadhesive Dosage Form (GMDF) is one type of Gastroretentive Drug Delivery System (GRDDS) technology designed to exploit the adhesiveness of dosage forms in the gastric mucosa. This aims to increase drug residence time, enhance drug solubility and absorption, and ultimately improve drug bioavailability and therapeutic effect. Various studies have explored the use of different polymers to develop GMDF systems and dosage forms. However, despite extensive research in this field, there are still limited GMDF products approved by the US FDA and INA FDA. Therefore, this review addresses the challenges in developing GMDF, its current state, and potential future opportunities. This literature review is performed by searching Google Scholar, PubMed, and ScienceDirect and Google Patents using the terms “gastroretentive”, “mucoadhesive”, “challenge”, “strategy”, and “patent.” Additionally, searches were conducted in the US FDA and INA FDA Drug Approval Databases. Based on our study, we identified numerous challenges in developing GMDF, including patient physiological challenges, drug formulas, production processes, product analysis, and clinical trials. To address these challenges, multiple strategies should be developed to optimize the formulation, production process, and product analysis of GMDF, ultimately leading to successful clinical trials and regulatory approval of this product.